Ethos : pour une mise au point conceptuelle et méthodologique - Reindert Dhondt; Beatrijs Vanacker (Contextes)
By way of theoretical prelude to the case-studies collected in this issue, the present article proposes a clarification of the concept of ethos and its related concepts, as well as of the definitional and methodological challenges they present. From the outset, this contribution adopts a double approach: it proposes a historical survey of the notion of ethos and the authorial figure in general, before formulating some methodological considerations. On the one hand, these reflections originate from a notional vagueness, which seems to subsist in the research on the author figure, in spite of – or perhaps because of – multiple attempts to clarify the variety of definitions proposed by the specialists concerned. On the other hand, the article touches upon different methodological problems, which derive from the confrontation of different conceptions of the author figure or from their application in case-studies of which the historical, generic and discursive diversity needs to be taken more fully into account.